Zwoływanie wyobraźni - Balcerzan, Edward (Wydawnictwo Poznańskie Studia Polonistyczne i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The term “imagination” has numerous meaning: colloquial, paraliterary, scientific. They all refer to auto-communication, which is a conversation of an individual with him or herself, when our mind faculties: memory, intuition, observation, intelligence, knowledge – and imagination, too – compete for dominance or strive for harmonious cooperation. Similarly to the generally understood imagination, its particular, important species (literary imagination) requires internal classification, because it is always an imagination of role: of the author, the reader, the expert, the performer, the censor, the distributor, or sometimes of the translator. The question of translator’s and author’s status provokes a comparison between author’s and translator’s imagination: they share some qualities, but also have decidedly different ones. The opposition between created nature and creating nature, which is a notion used by Józef Czechowicz, might be helpful in capturing the similarities and differences. But this opposition, too, demands a literary and historical context. The author created by the romantic myth seems someone gifted with imagination creating literary worlds, which are limitless, whereas the author of realist works, especially diaries, must give priority to observation, when a piece of external, empirical reality is described and recorded. Baroque, romanticism, realism, expressionism, avant- garde, postmodernism differ in their canons of imagination. The creative process by the author of an original work becomes a negotiation between innovations of authorial fantasy and recreation of the canon. The translator is under much stronger pressure from his or her times, because his or her objectives and tasks are different. Usually, knowledge is enough for a translator: linguistic, historical, literary, common, encyclopaedic, specialised. If knowledge fails, the translator reaches out to imagination as an instrument for interpretation of source text, but this happens only when the text is ambiguous and rich in images. Be it as it may, the quality and range of translator’s activity are determined by someone else’s imagination, accumulated in the translated work, and present in its rhetorics.
Calling in imagination
Keywords: auto-communication; literary communication; authorial literature; translation literature; author’s imagination; translator’s imagination